1975
DOI: 10.1007/bf00447111
|View full text |Cite
|
Sign up to set email alerts
|

Pichia lindnerii sp. n., eine neue Methanol assimilierende Hefe aus Erde

Abstract: A new undescribed species of yeast could be detected in forest soils in the area of Berlin, Germany. A description of the new homothallic species including latin diagnosis is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1976
1976
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…P. aphidis was first isolated from aphid secretions (Henninger and Windisch, 1975) and later identified on plant surfaces as well (Allen et al, 2004). Recently the sequence of P. aphidis isolate DSM70725 that was isolated from aphid secretions was published (Lorenz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…P. aphidis was first isolated from aphid secretions (Henninger and Windisch, 1975) and later identified on plant surfaces as well (Allen et al, 2004). Recently the sequence of P. aphidis isolate DSM70725 that was isolated from aphid secretions was published (Lorenz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudozyma antarctica and Pseudozyma prolifica) have suggested that those species hold great potential for biocontrol applications and production of novel fatty acids that may be useful for cosmetics and other industries . P. aphidis is a close relative of P. rugulosa (Begerow et al, 2000), which was first isolated from aphid secretions (Henninger and Windisch, 1975), but was later also identified on plant surfaces (Allen et al, 2004). reported that P. aphidis isolated from aphid secretions (isolate CBS 517.83) is not associated with colony collapse of powdery mildew, and that it does not produce unique antifungal fatty acids.…”
mentioning
confidence: 99%
“…media. meyerae, misumiaensis;" mucosa, naganishii, nakasei, ofunaensis;" philodendra," saitoi, sorbitolphila, spartinae and sydowiorum," b (I) Barnett et aI., 1983; (2) this paper, Bridges et aI., 1984;(8) Phaff and Knapp, 1956;(9) Shehata et aI., 1955;(10) Hedrick and Burke, 1950;(II) Kodama, 1974;(12) da Cunha et aI., 1957; (13) Starmer et aI., 1984;(14) Phaff et aI., 1972;(15) Starmer et aI., 1978b; (16) Nakase and Komagata, 1971;(17) Miller el aI., 1960;(18) (19) Billon-Grand, 1981;(20) Starmer et aI., 1982;(21) Price et aI., 1978;(22) Ladder, 1970;(23) Fuson et aI., 1980;(24) Bowles and Lachance, 1983;(25) Lachance et aI., 1982;(26) Phalf et aI., 1978;(27) Kurtzman et aI., 1979;(28) Henninger and Windisch, 1975;(29) Kobayashi, 1953;(30) Lee and Komagata, 1980;(31) Miranda et aI., 1982;(32) Holzschu et aI., 1979;(33) Starmer et aI., 1979;(34) Nakase and Komagata, 1970;(35) Phaff'et aI., 1983;(36) Holzschu et aI., 1983;(37) Santa Maria and Garcia Aser, 1977;(38) Phalfet aI., 1964;…”
Section: Methodsunclassified